Nikos Kazantzakis and ’’Maya the Bee’’ - Μητροφάνης Γιάννης (Education Sciences, 2019)
Maya the Bee (1912) by the German journalist and writer W. Bonsels, is a neoromantic novel for children, which became quickly a major publishing and cinematic success in Republic of Weimar. This early sample of Crossover Literature chooses Kazantzakis 1930 among others to translate for children’s readership, and not only, in Greece of Interwar. Kazantzakis as translator discovers in Bonsel’s hybrid narrative his self-image. The comparison with the original text and the much later translation of R. Kartheou (1980) highlights Kazantzakis’ multiple narrative strategy of cultural domestication, constructs a different implied reader than that of Bonsels. Kazantzakis’ ‘’Maya the Bee’’ adapts not only the adult reader expectations of Greece in Interwar period but also to the translator’s self-image.